Unhappy working with men? Workplace gender diversity and employee job-related well-being in Britain ; a WERS2004 based analysis - Getinet A. Haile (Institute for the Study of Labor (IZA), 2009)
This paper attempts to establish empirically the link between workplace gender diversity and employee job-related well-being. Using nationally representative linked employer-employee data for Britain, I employ econometric techniques that account for unobserved workplace heterogeneity. I find that gender diversity is associated with lower employee well-being among women in several of the equations estimated. The magnitudes of the estimated effects also tend to increase with (women's) group size. Workplace equality policies do not appear to ameliorate these effects.
urn:nbn:de:101:1-20090330104
Keywords: J16; J82; J7; I31; 330; Gender diversity; job-related well-being; linked employer-employee data; Britain; Arbeitsbedingungen; Geschlecht; Arbeitszufriedenheit; Frauenpolitik; Großbritannien